Photovoltaic Generator Approach Model for Characteristic Estimation I-V - Suwarno Suwarno; Rini Sadiatmi; Aminah Asmara Dewi; Herman Birje (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2023)
Modeling of the photovoltaic (PV) approach is generally described by nonlinear equations with solving the equation using the steps iteratively.  However, this proposed research discusses the monocrystal type PV module approach model to estimate the characteristics of a photovoltaic generator, because it has the advantage that it is good enough to operate in Indonesia. This approach model takes into account the relationship between power, energy, and current to obtain the performance characteristics of the PV generator. This PV generator approach model is compared with PV generator manufacturer data and analyzed to validate the proposed approach model. Approach model with simulation hope this helps to find out IV characteristics according to the data recorded on the PV module and can save time or reduce the time to measurement results. The simulation results obtained the amount of power, energy, and current, 200.475W, 133.65 W/m2, and 7.9 Amperes, respectively with a simulation time of about 1.5 milliseconds. In addition to the above results, a comparison between the current and the power of the PV modules under study is also given and it gives the result that at a certain current the power level will no longer increase, but the power will decrease drastically due to heat from the PV panel module, because the module has the ability to receive heat from outside.